THE CONCEPT AND SKILLS OF COMPUTATIONAL THINKING IN DIGITAL EDUCATION - Kamalova Г.Б.; Akzholova А.А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
Nowadays, the role of digital technologies in human life and in the field of education is increasing. The concept of computational thinking is becoming a key concept in the digital age. The use of such thinking in the educational process allows students to solve problems and tasks, creatively and systematically perceive various information. The article deals with the concept of "computational thinking", elements of computational thinking (abstraction, decomposition, generalization, algorithms), approaches to evaluating computational thinking. The article is based mainly on the review and analysis of foreign scientific and pedagogical works, since the practical definition of the concept of computational thinking and its components is not widely reflected in the works of Kazakhstani researchers.